Potential Application of Chimeric Antigen Receptor (CAR)-T Cell Therapy in Renal Cell Tumors - Schepisi, Giuseppe; Conteduca, Vincenza; Casadei, Chiara; Gurioli, Giorgia; Rossi, Lorena; Gallà, Valentina; Cursano, Maria Concetta; Brighi, Nicole; Lolli, Cristian; Menna, Cecilia; Farolfi, Alberto; Burgio, Salvatore Luca; et al. (Frontiers in Oncology, 2020)
Currently, renal cell carcinoma is characterized by interesting benefits from immunotherapy, leading to significant results in treatment outcome. In the latest years, the approval of nivolumab primarily as second-line monotherapy and, more recently, the approval of new combination therapies as first line treatment have already ascertained the importance of immunotherapy in this type of tumor. In this context, the Chimeric Antigen Receptor (CAR) -T represents a further step forward in the field of immunotherapy. First tested on hematological malignancies, this new therapeutic approach is increasingly becoming a topic of interest also for solid tumors. In this review, we provide the rationale and preliminary results of CAR-T cell therapy in renal cell malignancies.